USES OF DIGITAL TECHNOLOGIES IN ENGLISH LANGUAGE LETTERING PRACTICES BY HIGH SCHOOL STUDENTS - Pisetta, Cleide Beatriz Tambosi; Barbosa, Isabela Vieira; Fischer, Adriana (fólio - revista de letras, 2020)
Digital technologies are daily in people's lives and have been contributing to learning other languages. The aim of this paper is to understand the use of digital technologies in English language literacy practices by high school students. Through social network screenshots and game chat, as well as semi-structured group interviews. It was possible to analyze interactions of high school students with colleagues from other countries, positions about the use of English in and out of school, as well as evidence of school conditions of English language teaching. Data analysis is based on approaches to literacy studies and digital technologies, which recognize the value of new technologies not only in the classroom but also in vernacular practices. For the research subjects, learning that takes place within the virtual environment, specifically in online games, is characterized as autonomous and interactive, while classroom practices are perceived as providing the opportunity to learn standard English writing. However, although students point to the school and the internet as distant, subjects do not deny the school's contributions to English language learning, but do not establish a link between vernacular online gaming practices and dominant school practices.